2022
DOI: 10.3389/fonc.2022.832047
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Histone Post-Translational Modifications in Merkel Cell Carcinoma

Abstract: Merkel Cell Carcinoma (MCC) is a rare but highly aggressive form of non–melanoma skin cancer whose 5-year survival rate is 63%. Merkel cell polyomavirus (MCPyV), a small DNA tumor virus, is the etiological agent of MCC. Although representing a small proportion of MCC cases, MCPyV-negative MCCs have also been identified. The role of epigenetic mechanisms, including histone post-translational modifications (PTMs) in MCC, have been only partially determined. This review aims to describe the most recent progress o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 114 publications
0
29
0
Order By: Relevance
“…Modulation of these dynamics by histone post-translational modifications, histone variants, and interactions with chromatin proteins is an essential mechanism of epigenetic regulation of gene expression [ 3 ]. Dysregulation of nucleosome dynamics through mutations or aberrant histone post-translational modifications is associated with human disease, particularly cancer [ 4 , 5 ]. Such dynamical modes as DNA wrapping/unwrapping, nucleosome sliding, H2A-H2B dimer exchange are known to affect transcription factor binding [ 6 , 7 ], transcription by Pol II through nucleosomes [ 8 ], higher-order chromatin architecture [ 9 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of these dynamics by histone post-translational modifications, histone variants, and interactions with chromatin proteins is an essential mechanism of epigenetic regulation of gene expression [ 3 ]. Dysregulation of nucleosome dynamics through mutations or aberrant histone post-translational modifications is associated with human disease, particularly cancer [ 4 , 5 ]. Such dynamical modes as DNA wrapping/unwrapping, nucleosome sliding, H2A-H2B dimer exchange are known to affect transcription factor binding [ 6 , 7 ], transcription by Pol II through nucleosomes [ 8 ], higher-order chromatin architecture [ 9 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Given the important role of HDAC in modulating antitumour immune response in various cancers [ 58 , 66 , 67 , 68 ], the combination of HDACi with other therapeutic agents gains its popularity. In the present study, we demonstrated that belinostat, dacinostat, givinostat, and panobinostat enhanced CTL sensitivity in SW1990 CTLr and BxPC3 CTLr cells ( Figure 4 A, p value < 0.01), suggesting that the antitumour effects of CTL can be enhanced by HDACi.…”
Section: Discussionmentioning
confidence: 99%
“…The currently employed gold standard and most broadly used molecular method worldwide for the detection of active SARS-CoV-2 infection is RT-PCR [26,45,46]. The RT-PCR assay is a broadly employed molecular biology technique which allows for the analysis and quantification of nucleic acids for a large variety of applications [47][48][49]. The method is performed on nasopharyngeal and oropharyngeal swabs, which are the preferred sampling method of the World Health Organization (WHO) and the Centers for The detection of active SARS-CoV-2 infection is performed using molecular diagnostics, i.e., real-time reverse transcriptionpolymerase chain reaction (RT-PCR), droplet-digital PCR (ddPCR), clustered regularly interspaced short palindromic repeats (CRISPR) and next-generation sequencing (NGS), in order to detect the viral RNA during the first weeks after the emergence of symptoms.…”
Section: Real-time Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%
“…The currently employed gold standard and most broadly used molecular method worldwide for the detection of active SARS-CoV-2 infection is RT-PCR [26,45,46]. The RT-PCR assay is a broadly employed molecular biology technique which allows for the analysis and quantification of nucleic acids for a large variety of applications [47][48][49]. The method is performed on nasopharyngeal and oropharyngeal swabs, which are the preferred sampling method of the World Health Organization (WHO) and the Centers for Disease Control and Prevention (CDC), although it can be underlined that oral throat wash (OTW) is an additional and less invasive, safer as well as more efficient sample-collection approach.…”
Section: Real-time Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%